Construction of the EFL Mobile Learning Model in the Hybrid Distributed Terminal. (12th January 2022) - Qu, Lijie; Song, Shihui; Xiao, Zuochun
Abstract : With the integration of technology in higher education, mobile learning plays an important role in EFL classes. In order to optimize the efficiency of EFL learning, a mobile learning model in the hybrid distributed terminal is constructed. The online platform supporting both synchronous and asynchronous learning with three types of interaction helps build a blended learning model and creates a closed loop for ubiquitous online and offline learning with multiple evaluation, which also builds a community of inquiry-based learning to facilitate collaborative study and deep thinking. Aiming to improve the resource scheduling performance of learning information sharing mode, based on the traditional sharing mode hardware, the mobile learning software for the hybrid distributed terminal is thus optimized. Learning resources are mined and fused to realize the scheduling of learning information resources, and user interface management function is designed to construct the EFL mobile learning mode with the hybrid distributed terminal.